2009
DOI: 10.1111/j.1468-3083.2008.02971.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biological factors predictive of malignancy in dermatomyositis

Abstract: EditorAlthough the paraneoplastic nature of a subset of dermatomyositis (DM) cases is unquestionable, the factors that indicate the coexisting cancer still remain unclear. Several predictive signs have been postulated as a marker of underlying malignancy: older age, male gender, rapid onset of the disease, presence of cutaneous necrosis, increased erythrocyte sedimentation rate (ESR), and increase or normality of creatine phosphokinase (CPK). [1][2][3][4][5][6][7][8] In order to identify potential risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 7 publications
1
28
1
1
Order By: Relevance
“…Of the included studies, 13 studies[19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31] considered age as a variable. Out of these 13 studies, two studies[29], [30] provided age group-specific data: data for patients younger than 45 and data for patients 45 and older.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the included studies, 13 studies[19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31] considered age as a variable. Out of these 13 studies, two studies[29], [30] provided age group-specific data: data for patients younger than 45 and data for patients 45 and older.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis of 11 studies[19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [31] indicated that malignancy associated with PM/DM was associated with older age (WMD 10.93, 95% CI: 9.34 to 12.52). For patients with DM only,[19], [20], [21], [22], [23], [24], [25], [31] a similar difference was observed in data pooled from the eight relevant studies (WMD 10.63, 95% CI: 8.92 to 12.33). As noted, two estimates[29], [30] from two studies of PM/DM patients divided the subjects according to age by using “45” as the age divider.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations